High-Performance 3-Phase 5-Level E-Type Multilevel–Multicell Converters for Microgrids - Marco di Benedetto; Alessandro Lidozzi; Luca Solero; Fabio Crescimbini; Petar J. Grbović (Energies, 2021)
This paper focuses on the analysis and design of two multilevel–multicell converters (MMCs), named 3-phase 5-Level E-Type Multilevel–Multicell Rectifier (3Φ5L E-Type MMR) and 3-phase 5-Level E-Type Multilevel–Multicell Inverter (3Φ5L E-Type MMI) to be used in microgrid applications. The proposed 3-phase E-Type multilevel rectifier and inverter have each phase being accomplished by the combination of two I-Type topologies connected to the T-Type topology. The two cells of each phase of the rectifier and inverter are connected in interleaving using an intercell transformer (ICT) in order to reduce the volume of the output filter. Such an E-Type topology arrangement is expected to allow both the high efficiency and power density required for microgrid applications, as well as being capable of providing good performance in terms of quality of the voltage and current waveforms. The proposed hardware design and control interface are supported by the simulation results performed in Matlab/Simulink. The analysis has been then validated in terms of an experimental campaign performed on the converter prototype, which presented a power density of 8.4 kW/dm3 and a specific power of 3.24 kW/kg. The experimental results showed that the proposed converter can achieve a peak efficiency of 99% using only silicon power semiconductors.